FIGURATIVE LANGUAGE IN A SHORT STORY ENTITLED “AN ANGEL IN DISGUISE” - Dwi Iswahyuni; Sri Rejeki; Angela Bayu Pertama Sari; Devita Widyaningtyas Yogyanti (IKIP Siliwangi, 2024)
This study endeavored to find out the types of figurative language in a short story entitled “An Angel in Disguise” and the most frequent occurrence of the figurative language type. This short story was chosen because it contained good moral values. The method employed in this study was a descriptive qualitative method. The steps in analyzing data in this study encompassed reading the short story, looking for the phrases or sentences that belonged to figurative language, classifying those phrases or sentences based on the types of figurative language, interpreting the figurative language found, drawing the conclusions. The results showed that there were several types of figurative languages found in the short story. They were personification, metaphor, hyperbole, and simile. Moreover, the most frequent occurrence was hyperbole. The use of exaggeration (hyperbole) in the short story can make the readers excited in reading it and avoid the readers’ boredom. Furthermore, this short story can be used as learning materials for Senior High School students as it can enrich students’ insights about narrative text and how to make a story interesting.